Mitochondria-Associated Gene SLC25A32 as a Novel Prognostic and Immunotherapy Biomarker: From Pan-Cancer Multiomics Analysis to Breast Cancer Validation - Shiqi Zuo; Siyuan He; Zhiqin Zhu; Yingying Zhang; Yanjie Hou; Ziqing Wu; Yao Tang (Analytical Cellular Pathology)
Background. Mutations in SLC25A32 in humans cause late-onset exercise intolerance, which is associated with various neurological and metabolic diseases. However, its specific mechanism of action in tumour development is poorly understood owing to the lack of multiomics integrated analysis of SLC25A32 in pan-cancer. Methods. We used various analytical tools to comprehensively investigate the transcription, protein level, and promoter methylation of SLC25A32. Furthermore, the GSCA and cBioPortal databases were used to evaluate the inheritance impact and epigenetic alterations of SLC25A32 in pan-cancer. SLC25A32 expression and the prognostic significance of copy number alterations in multiple cancers were compared using the UCSCXenaShiny and GEPIA2.0 platforms, and its specific function in breast cancer was experimentally verified. Results. SLC25A32 is abnormally expressed at the transcriptional and protein levels in most cancer types, with aberrant DNA promoter methylation and significant gene amplification in most tumours. SLC25A32 is significantly associated with the survival prognosis of some cancers, immune infiltrating cells, tumour stemness, and immune-related markers. SLC25A32 knockdown decreased breast tumour cell proliferation, invasion, and metastasis. Conclusions. This study aimed to reveal SLC25A32 as a novel prognostic biomarker for pan-cancer prediction and immunotherapy efficacy and specifically describes its underlying mechanism of action in breast cancer. SLC25A32 is widely differentially expressed in pan-cancer with prognostic significance and is correlated with immune infiltration. Additionally, it can affect breast cancer occurrence and development.